2009
DOI: 10.1002/lsm.20728
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous laser discectomy guided with stereotactic computer‐assisted surgical navigation

Abstract: This preclinical study demonstrates the clinical utility of a 980-nm diode laser delivered through a fiber-optic waveguide trocar in which precise insertion was enabled by the use of surgical navigation. This in turn decreases the exposure to ionizing radiation during the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Previous work by the authors evaluated the thermal‐induced changes by 980‐nm laser using standard magnetic resonance (MR) imaging 32. In the present study, we compared the 980‐nm wavelength diode laser effects with those of a 1,470‐nm wavelength diode laser using bovine spine cadavers ex vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by the authors evaluated the thermal‐induced changes by 980‐nm laser using standard magnetic resonance (MR) imaging 32. In the present study, we compared the 980‐nm wavelength diode laser effects with those of a 1,470‐nm wavelength diode laser using bovine spine cadavers ex vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Computer-aided fluoroscopic techniques [6, 9, 27, 29, 34] are among the various methodologies devised to increase the accuracy of screw placement; however, widespread adoption has been slow because of the increased set-up and operative times and lack of perceived benefit [3]. Electromagnetic field (EMF) navigation-based systems eliminate cumbersome optical array receivers as well as line-of-sight issues that can interfere with the normal flow of the operative procedure [10, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Sequeiros et al [24] reported on the use of MRI guidance to place a guidance needle to ablate osteoid osteomas. Von Jako and Cselik [25] described the use of a stereotactic computer-assisted surgical 16. Necrosis of the cranial portion of the L5 vertebra has been caused by the side-firing fiber system of the potassium triphosphide (KTP) laser.…”
Section: Radiologic Guidance For Needle Placementmentioning
confidence: 99%